Progressive collapse resistance of reinforced concrete structures - Lim, Mee Mee (2016)
There has been an increasing concern on progressive collapse of buildings with the increase in risks due to dangers from terrorist attacks. There are two most popular methods adopted in current building codes to mitigate such threats, namely indirect method and direct method. One of the direct methods is alternate load path (ALP) method. ALP is the more effective approach to study the structural resistance to progressive collapse. Hence, the ALP method is often used with column removal assumption to assess the occurrence of progressive collapse. There have been many studies done on the ALP of reinforced concrete structures using static procedures to examine structural resistance to progressive collapse. However, progressive collapse is a dynamic and non-linear event. Hence, to fully understand the realistic response of RC structures under progressive collapse, this project will focus on the study of dynamic response of RC sub-structures. Free-fall dynamic and contact detonation tests are the two dynamic tests which are proposed. For this project, it will only be focusing on the free-fall dynamic series. The main purpose of the tests is to compare structural behavior under quasi-static and dynamic conditions. The specimens are tested under different parameters such as the load level, boundary conditions, axial force in columns and the difference between point-loading and distributed-loading methods.